A lithium-ion battery
By coating the membrane surface with a functional layer of polyethylene oxide and amorphous polymer, a continuous ion transport channel is formed, which solves the problems of increased electrolyte viscosity and decreased ion transport capacity at low temperatures in lithium-ion batteries, and achieves high-efficiency discharge performance and stability in low-temperature environments.
Patent Information
- Application Number
- CN202611139945.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-11-03
AI Technical Summary
In low-temperature environments, the electrolyte viscosity of lithium-ion batteries increases sharply and the ion transport capacity decreases, resulting in a drastic deterioration in discharge performance, making it impossible to apply them on a large scale in high-altitude and cold-weather special scenarios.
A functional layer of polyethylene oxide and an amorphous polymer with a Tg≤-17℃ is coated on the surface of the diaphragm to form a continuous quasi-solid-state ion transport channel. The amorphous polymer chain segments are used to disrupt the low-temperature crystallization region of PEO, suppressing the aggregation of hydrogen bonds and the sudden increase in viscosity of the electrolyte, thereby constructing a continuous amorphous phase to improve ion conduction efficiency.
It significantly improves the ion conduction efficiency and discharge capacity of lithium-ion batteries in environments ranging from -40℃ to -20℃, solves the problem of low-temperature discharge performance degradation, and ensures battery cycle stability and safety.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a lithium-ion battery. Background Technology
[0002] Lithium-ion batteries, with their advantages of high energy density, long cycle life, and environmental friendliness, have been widely used in new energy vehicles, portable electronic devices, cryogenic energy storage, and special equipment. However, in low-temperature environments (-40℃ to 0℃), the battery's low-temperature discharge performance deteriorates sharply. The core issue lies in the sudden increase in electrolyte viscosity and a significant decrease in ion transport capacity at low temperatures. This problem has become a key bottleneck restricting its large-scale application in high-altitude and cold-weather special scenarios, and is also a core challenge in the current research and development of wide-temperature-range lithium-ion batteries. Under low-temperature conditions, the hydrogen bonding between electrolyte molecules is significantly enhanced, leading to solvent molecule aggregation and crystallization, and a sharp increase in system viscosity. On the one hand, this significantly reduces the lithium salt dissociation efficiency, resulting in a decrease in effective carrier concentration; on the other hand, it severely hinders the lithium-ion migration rate, leading to a significant decline in ion conduction efficiency. Ultimately, this results in a sharp reduction in battery discharge capacity, a decrease in discharge voltage, and even failure to function properly.
[0003] The solutions to the poor low-temperature performance of lithium-ion batteries mainly focus on the following three core directions: First, the direction of separator coating modification, attempting to coat the separator surface with inorganic solid electrolytes such as LATP and LLZO to improve low-temperature ion transport based on their ion conduction properties. However, these inorganic solid electrolytes have poor compatibility with electrolytes, high interfacial impedance, and are prone to agglomeration leading to ion channel blockage, thus limiting the effectiveness of low-temperature modification. Second, the direction of electrolyte additive optimization, attempting to reduce the performance of low-temperature batteries by adding vinylene carbonate (VC), fluoroethylene carbonate (FEC), or novel low-temperature additives. Weak electrolytes can achieve hydrogen bonding between molecules and lower the freezing point, but the amount of additives is difficult to control precisely. Excessive addition can easily trigger interfacial side reactions, damage the integrity of the SEI film, and affect the long-term cycle stability of the battery. Thirdly, there are adjustments to the electrolyte solvent system, such as replacing some high-freezing-point solvents (e.g., ethylene carbonate EC) with low-freezing-point solvents like dimethyl carbonate (DMC) and diethyl carbonate (DEC), or using mixed solvent systems to lower the electrolyte freezing point. However, these solvent systems often have drawbacks such as low dielectric constant and weak lithium salt dissociation ability, making it impossible to balance low-temperature and room-temperature performance. In addition, some research focuses on electrode material modification, improving low-temperature reaction kinetics by doping with metal elements or optimizing the electrode structure, but the processes are complex and costly. Summary of the Invention
[0004] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a lithium-ion battery in which a functional layer formed of polyethylene oxide-amorphous polymer is coated on the separator. This functional layer, with the help of the separator's porous structure, forms a continuous quasi-solid-state ion transport channel, which neither damages the separator's isolation function nor hinders the coating from peeling off, but also utilizes the separator's support to ensure the coating adheres firmly. Simultaneously, by utilizing the separator's sufficient contact characteristics with the electrolyte, the functional layer components directly act on the electrolyte system, achieving a synergistic adaptation of "separator support - functional layer function - ion transport." Moreover, at low temperatures, the crystallinity of polyethylene oxide (PEO) surges, ion transport channels break down, and the electrolyte exhibits a high viscosity due to hydrogen bond aggregation and crystallization. The amorphous polymer segments can interpenetrate within the PEO molecular network, efficiently disrupting the low-temperature crystallization region of PEO and constructing a continuous amorphous phase. Even at -40°C, sufficient free volume is retained, thereby significantly improving the low-temperature performance of the lithium-ion battery.
[0005] To solve the above-mentioned technical problems, the present invention is implemented as follows: According to one aspect of the present invention, a lithium-ion battery is provided, the lithium-ion battery comprising a housing and an electrode assembly and an electrolyte disposed within the housing; The electrode assembly includes a positive electrode, a negative electrode, and a separator, wherein the separator is disposed between the positive electrode and the negative electrode; The diaphragm includes a diaphragm substrate and a functional layer disposed on at least one surface of the diaphragm substrate along the thickness direction; The functional layer comprises polyethylene oxide and an amorphous polymer; the amorphous polymer has a Tg ≤ -17℃.
[0006] In some embodiments, the amorphous polymer includes at least one of polyethylene carbonate and polytrimethylene carbonate.
[0007] In some embodiments, the number-average molecular weight of the polyethylene oxide is 8,000 to 15,000.
[0008] In some embodiments, the number-average molecular weight of the amorphous polymer is 10,000 to 20,000.
[0009] In some embodiments, the mass ratio of the polyethylene oxide to the amorphous polymer is 1:(4~6).
[0010] In some embodiments, the functional layer further includes a modifier; the modifier includes a compound containing both hydroxyl and urea groups; preferably, the compound containing both hydroxyl and urea groups includes at least one of N-methyl-N'-hydroxyethyl urea, N,N'-bis(2-hydroxyethyl)-urea, and 1,3-dihydroxymethyl urea.
[0011] In some embodiments, the functional layer further includes a crosslinking agent; the crosslinking agent includes glycidyl ether; preferably, the glycidyl ether includes at least one of 1,4-butanediol diglycidyl ether, polypropylene glycol diglycidyl ether, and glyceryl triglycidyl ether.
[0012] In some embodiments, the functional layer has a relative crystallinity of 3% to 13% at -40°C.
[0013] In some embodiments, the single-layer coating thickness of the functional layer is 2μm to 10μm.
[0014] In some embodiments, the air permeability of the diaphragm is 200s / 100mL to 500s / 100mL.
[0015] In some embodiments, the electrolyte comprises an electrolyte salt and a solvent.
[0016] In some embodiments, the electrolyte salt includes at least one of LiPF6, LiBF4, LiFSI, and LiTFSI.
[0017] In some embodiments, the solvent includes at least one of ethylene carbonate, diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate.
[0018] Implementing the technical solution of the present invention has at least the following beneficial effects: 1. This invention provides a functional layer on the surface of a separator containing polyethylene oxide (PEO) and an amorphous polymer with a Tg ≤ -17℃. This layer allows for the formation of a continuous quasi-solid-state ion transport channel through the porous structure of the separator. Without compromising the separator's isolation function, the amorphous polymer segments interpenetrate and disrupt the low-temperature crystallization region of PEO, inhibiting low-temperature hydrogen bond aggregation, crystallization, and a sudden increase in viscosity of the electrolyte. This significantly reduces the lithium-ion migration barrier and greatly improves the ion conduction efficiency and discharge capacity in ultra-low temperature environments of -40℃ to -20℃, thus solving the core problem of the rapid deterioration of lithium battery discharge performance at low temperatures.
[0019] 2. In a preferred embodiment of the present invention, by limiting the amorphous polymer to at least one of polyethylene carbonate (PEC) and polytrimethylene carbonate (PTMC), and specifying the molecular weight of polyethylene oxide (PEO) and the amorphous polymer and their mass ratio of 1:(4~6), and combining it with a hydroxyl + urea bifunctional modifier and a glycidyl ether crosslinking agent, a stable covalent network can be formed, further enhancing the electrolyte's hydrogen bond regulation, lithium salt dissociation, and ion transport effects. Simultaneously, by limiting the functional layer's relative crystallinity at -40℃ to 3%~13%, single-layer thickness to 2~10μm, and separator permeability to 200~500s / 100mL, and combining it with an electrolyte containing 20wt%~40wt% EC, it can avoid separator pore blockage, coating peeling and agglomeration, and prevent ion channel breakage. This improves low-temperature discharge performance while ensuring battery cycle stability, rate performance, and safety, achieving a comprehensive balance between ultra-low temperature performance and conventional service performance.
[0020] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation
[0021] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0022] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0023] In the description of this application, "same chemical composition" should be interpreted broadly, that is, the main components of the two have the same chemical composition, or the two have substantially the same chemical composition, but may have errors or impurities within the acceptable range that can be understood by those skilled in the art.
[0024] In the description of this application, "A and / or B" can include any of the cases of A alone, B alone, or A and B, where A and B are merely examples and can be any technical feature connected by "and / or" in this application.
[0025] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0026] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0027] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.
[0028] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0029] Currently, to address the poor low-temperature performance of lithium batteries, previous research has been extensive, mainly focusing on three core directions: First, the modification of separator coatings, attempting to coat the separator surface with inorganic solid electrolytes such as LATP and LLZO to improve low-temperature ion transport based on their ion conduction properties. However, these inorganic solid electrolytes have poor compatibility with electrolytes, high interfacial impedance, and are prone to aggregation leading to ion channel blockage, resulting in limited low-temperature modification effects. Second, the optimization of electrolyte additives, through the addition of vinylene carbonate (VC), fluoroethylene carbonate (FEC), or novel low-temperature additives. Additives are used to weaken intermolecular hydrogen bonds in the electrolyte and lower the freezing point, but the dosage is difficult to control precisely. Excessive addition can easily trigger interfacial side reactions, damage the integrity of the SEI film, and affect the long-term cycle stability of the battery. Thirdly, the direction of electrolyte solvent system adjustment includes replacing some high-freezing-point solvents (such as ethylene carbonate EC) with low-freezing-point solvents such as dimethyl carbonate (DMC) and diethyl carbonate (DEC), or using mixed solvent systems to lower the electrolyte freezing point. However, such solvent systems often have defects such as low dielectric constant and weak lithium salt dissociation ability, making it impossible to balance low-temperature performance and room-temperature performance. In addition, some research focuses on electrode material modification, improving low-temperature reaction kinetics by doping with metal elements or optimizing the electrode structure, but the process is complex and costly.
[0030] In existing liquid lithium battery technologies, polyethylene oxide (PEO) is widely used. The ether radical groups in its molecular chain can promote lithium salt dissociation and construct preliminary ion transport channels. It is also widely available, low-cost, and easily blended and modified. However, PEO has inherent drawbacks: at low temperatures, its molecular chain mobility decreases, crystallinity surges, chain segments freeze, and free volume shrinks, leading to difficulties in lithium salt dissociation and breakage of ion transport channels. Furthermore, it cannot regulate intermolecular hydrogen bonds in the electrolyte, failing to suppress low-temperature crystallization and a sudden increase in viscosity. Using it alone or through conventional modification cannot overcome the low-temperature bottleneck. This patent prioritizes the modification of PEO with polyethylene carbonate (PEC), with polytrimethylene carbonate (PTMC) as an alternative. Through synergistic effects, the above problems are addressed. The modified system is specifically coated onto the membrane surface to maximize its synergistic effect with the electrolyte and membrane.
[0031] Previous studies have significant limitations, failing to establish an integrated system capable of synergistically controlling ion dissociation, transport channels, and electrolyte aggregation. Based on this, this invention patent develops a covalent network coating material consisting of "PEO-PEC (preferred) / PTMC / PPC (alternative)-crosslinking agent-hydroxyethyl urea." The core principle is to leverage the stable structure of the covalent network to fully utilize the synergistic effects of each component with the separator and electrolyte, fundamentally improving the low-temperature discharge performance of lithium batteries and filling a technological gap.
[0032] According to one aspect of the present invention, a lithium-ion battery is provided, the lithium-ion battery including a housing and an electrode assembly and an electrolyte disposed within the housing; The electrode assembly includes a positive electrode, a negative electrode, and a separator, with the separator disposed between the positive electrode and the negative electrode. The diaphragm includes a diaphragm substrate and a functional layer disposed on at least one surface of the diaphragm substrate along the thickness direction; The functional layer comprises polyethylene oxide and an amorphous polymer; the amorphous polymer has a Tg ≤ -17℃.
[0033] This invention addresses the core problem of rapidly deteriorating lithium battery discharge performance at low temperatures by creating a functional layer on the surface of a separator containing polyethylene oxide (PEO) and an amorphous polymer with a Tg ≤ -17℃. This layer utilizes the porous structure of the separator to form a continuous quasi-solid-state ion transport channel. Without compromising the separator's isolation function, the amorphous polymer chain segments disrupt the low-temperature crystallization region of PEO, inhibiting low-temperature hydrogen bond aggregation, crystallization, and a sudden increase in viscosity of the electrolyte. This significantly reduces the lithium-ion migration barrier and substantially improves ion conduction efficiency and discharge capacity in ultra-low temperature environments of -40℃ to -20℃.
[0034] In embodiments of the present invention, the amorphous polymer includes at least one of polyethylene carbonate and polytrimethylene carbonate. Preferably, the amorphous polymer is PEC. PEC is an amorphous polymer whose chain segments can efficiently intercalate into the PEO molecular network, disrupting the low-temperature crystallization region of PEO. It can still construct a continuous amorphous phase and retain sufficient free volume at -40°C. Its carbonate groups synergistically interact with the ether oxygen groups of PEO to polarize lithium salt ion pairs and promote lithium salt dissociation. At the same time, it forms a weak interaction with the electrolyte solvent, breaking the solvent hydrogen bond network, inhibiting solvent crystallization and viscosity surge, and ultimately reducing the lithium ion migration barrier, achieving synergistic optimization of ion dissociation, transport channels, and electrolyte regulation.
[0035] In embodiments of the present invention, the number-average molecular weight of polyethylene oxide is preferably 8,000 to 15,000. For example, the number-average molecular weight of polyethylene oxide can specifically be selected as 8,000, 12,000, 15,000, or any value between the two mentioned above.
[0036] In embodiments of the present invention, the number-average molecular weight of the amorphous polymer is preferably 10,000 to 20,000. For example, the number-average molecular weight of the amorphous polymer can be specifically selected as 10,000, 15,000, 20,000, or any value between the two.
[0037] It should be noted that if the molecular weight of polyethylene oxide and amorphous polymer is too large, the molecular chains will be severely entangled, the chain segment mobility will be insufficient at low temperatures, local crystalline regions will easily form, destroy the amorphous continuous phase, and hinder ion transport; if the molecular weight is too small, the coating layer will not have sufficient mechanical strength, will easily fall off the membrane surface, and the number of lithium salt coordination sites will be insufficient, resulting in a significant decrease in ion conduction efficiency.
[0038] In embodiments of the present invention, the mass ratio of polyethylene oxide to amorphous polymer is preferably 1:(4-6). For example, the mass ratio of polyethylene oxide to amorphous polymer may specifically be 1:4, 1:5, 1:6, or any ratio between the two mentioned above.
[0039] It should be noted that an excessively high proportion of PEO will lead to severe low-temperature crystallization and obstruction of ion transport channels, while an excessively low proportion will result in insufficient lithium salt coordination sites and reduced ion conduction efficiency. This ratio can fully utilize the crystallization-inhibiting effect of PEC while ensuring sufficient ion coordination and transport sites, perfectly adapting to the stable construction of hydroxyethyl urea modification and covalent networks.
[0040] In embodiments of the present invention, the functional layer further includes a modifier; the modifier includes compounds containing both hydroxyl and urea groups; preferably, the compounds containing both hydroxyl and urea groups include at least one of N-methyl-N'-hydroxyethyl urea, N,N'-bis(2-hydroxyethyl)-urea, and 1,3-dihydroxymethyl urea.
[0041] In embodiments of the present invention, the functional layer further includes a crosslinking agent; the crosslinking agent includes glycidyl ether; preferably, the glycidyl ether includes at least one of 1,4-butanediol diglycidyl ether, polypropylene glycol diglycidyl ether, and glyceryl triglycidyl ether.
[0042] In embodiments of the present invention, the relative crystallinity of the functional layer at -40°C is preferably 3% to 13%. A crystallinity greater than 13% will cause severe low-temperature crystallization of PEO and breakage of continuous ion transport channels, directly leading to a significant decrease in the battery's low-temperature discharge capacity, charge-discharge efficiency, and cycle stability. A crystallinity less than 3% requires a significant reduction in the proportion of PEO, which will result in insufficient lithium salt coordination sites, a decrease in the coating's mechanical strength and resistance to electrolyte swelling, and conversely, weaken the low-temperature lithium-ion transport efficiency and the long-term service stability of the coating.
[0043] For example, the relative crystallinity of the functional layer at -40°C can be specifically selected as 3%, 4.3%, 6%, 7%, 7.2%, 7.5%, 8.1%, 8.3%, 8.9%, 12.5%, 13%, or any value between the two mentioned above.
[0044] In embodiments of the present invention, the thickness of a single coating layer of the functional layer is preferably 2 μm to 10 μm. The coating method can be single-layer or double-layer coating. If the coating is too thick, the membrane pores will be excessively blocked, significantly increasing ion transport resistance, raising the battery's internal resistance, and reducing rate performance; the internal stress of the coating will increase, making it prone to cracking and peeling; the ion transport path will be too long, reducing low-temperature conductivity and lowering the overall energy density of the battery. If the coating is too thin, the coating will be discontinuous, failing to form a complete and continuous PEO-PEC-crosslinker-hydroxyethyl urea covalent network, significantly weakening its effects on low-temperature crystallization inhibition of the electrolyte, lithium salt dissociation promotion, and ion conduction channel construction, resulting in the failure of low-temperature modification effects; the coating will also have poor resistance to electrolyte swelling, easily dissolving and breaking, and unable to maintain stable function over a long period.
[0045] For example, the single-layer coating thickness of the functional layer can be specifically selected as 2μm, 5μm, 10μm or any value between the two mentioned above.
[0046] In a specific embodiment of the present invention, the method for preparing the functional layer includes the following steps: Raw material preparation and pretreatment: Select commercial PEO and commercial amorphous polymer, and weigh them at a mass ratio of 1:4 to 1:6; select N,N-dimethylformamide (DMF) or N-methyl-2-pyrrolidone (NMP) as the blending solvent.
[0047] Solution blending and compatibility enhancement: Pretreated PEO and amorphous polymer are simultaneously added to DMF or NMP solvent, and the temperature is raised to 30-50℃ (if the temperature is too high, the thermal motion of PEO molecular chains will intensify, and local crystallization and aggregation will easily occur, destroying the amorphous continuous phase; the amorphous polymer chain segments may undergo thermal degradation, the activity of carbonate groups will decrease, and the compatibility with PEO will decrease, leading to phase separation of the blend system; if the temperature is too low, the mobility of PEO and amorphous polymer molecular chains will be insufficient, the chain segments will have difficulty interpenetrating, and a uniform blend network cannot be formed). The stirring speed is 300-500 r / min, and the mixture is stirred at a constant temperature for 3-4 h, while simultaneously ultrasonic dispersion at 300-500 W for 1.0-1.5 h to promote uniform interpenetration and compatibility of PEO and amorphous polymer molecular chains, forming a continuous amorphous blend system.
[0048] The above blend system was kept at 30-50℃ (if the temperature is too high, the epoxy ring-opening reaction rate will be too fast, the cross-linking network will be unevenly formed, and local gelation will easily occur; if the temperature is too low, the epoxy group activity of the cross-linking agent will be insufficient, the cross-linking reaction will be incomplete, the covalent network strength will be poor, and the coating's resistance to electrolyte swelling will be reduced). A cross-linking agent was added in proportion (the amount of cross-linking agent is 1% to 3% of the total mass of PEO and amorphous polymer. If the amount is too high, the cross-linking will be excessive, leading to coating embrittlement, blockage of membrane pores, and obstruction of ion transport channels; excessive epoxy groups are prone to side reactions with lithium salts in the electrolyte, damaging the integrity of the SEI membrane and reducing cycle stability; the viscosity of the system will increase sharply, and the coating processability will deteriorate. If the amount is too low, the covalent bonding force between PEO-amorphous polymer and modifier will be weak, and the coating will easily fall off the membrane). Subsequently, a modifier (PEO, 5%~10% of the total mass of the amorphous polymer) is added. Excessive dosage leads to excessive aggregation of intermolecular hydrogen bonds, resulting in self-agglomeration and preventing uniform dispersion in the coating; excessive urea groups may form strong coordination with lithium salts, hindering lithium-ion desolvation; and compete with the crosslinking agent for reaction sites, leading to an incomplete crosslinking network. Insufficient dosage results in insufficient hydrogen bond regulation, failing to effectively break the intermolecular hydrogen bond network of the electrolyte solvent, leaving the problems of solvent crystallization and viscosity surge at low temperatures unresolved; weak modification of the lithium-ion solvated sheath layer, no reduction in ion migration activation energy, and limited improvement in low-temperature discharge performance.
[0049] Continue to keep warm at 30~50℃ and stir at a constant temperature for 2~3 hours. At the same time, ultrasonically disperse at 300~500W and 30~50kHz for 30 minutes to promote the ring opening of epoxy groups and the formation of covalent bonds, and finally form a covalent network of "PEO-PEC-crosslinking agent-hydroxyethyl urea".
[0050] After the reaction is complete, cool to room temperature and stir for 20-40 minutes to stabilize the system. Detect the solution viscosity (controlling it between 500-5000 mPa·s to suit coating requirements). If the viscosity is too high, add a small amount of DMF or NMP solvent to adjust it to the target range to obtain a hydroxyethyl urea modified PEO-PEC mother liquor that can be directly used for coating.
[0051] The preparation of the coated diaphragm requires a pretreatment-coating-drying and curing process. First, the polyolefin diaphragm raw material (PE or PP base film, or PE or PP diaphragm coated with ceramic / bombre or other materials) is heat-treated at 60-80℃ in a vacuum environment (vacuum degree: 0.01-0.015MPa) for 60-120 minutes to remove surface adsorbed moisture and is then ready for use. Subsequently, a microgravure coating method is used to coat both sides of the diaphragm with hydroxyethyl urea-modified PEO-PEC mother liquor, controlling the dry film thickness to be 2-10μm. After coating, it is heat-treated at 60-80℃ in a vacuum environment for 60-120 minutes (vacuum degree: 0.01-0.015MPa). After drying, the diaphragm is placed in a drying environment to cool to room temperature for later use.
[0052] In embodiments of the present invention, the air permeability of the diaphragm is preferably 200s / 100mL to 500s / 100mL. Excessive air permeability indicates that the pores of the diaphragm are excessively blocked, significantly increasing ion transport resistance and deteriorating the battery's internal resistance and rate performance; insufficient air permeability indicates insufficient coating continuity and uniformity, making it difficult to guarantee the low-temperature modification effect and structural stability.
[0053] For example, the permeability of the diaphragm can be specifically selected as 200s / 100mL, 350s / 100mL, 500s / 100mL or any value between the two mentioned above.
[0054] In embodiments of the present invention, the electrolyte comprises an electrolyte salt and a solvent. The present invention does not impose any particular limitation on the source of the electrolyte salt and solvent; commercially available products well known to those skilled in the art can be used.
[0055] In embodiments of the present invention, the electrolyte salt includes at least one of LiPF6, LiBF4, LiFSI, and LiTFSI.
[0056] In embodiments of the present invention, the solvent includes at least one of ethylene carbonate, diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate, preferably a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC), wherein the mass percentage of ethylene carbonate (EC) in the mixed solvent is preferably 20% to 40%. This content allows EC to form strong hydrogen bonds with hydroxyethyl urea in the membrane functional layer, and works in conjunction with the ether oxygen and carbonate groups of PEO-PEC / PTMC / PPC in the functional layer to break the low-temperature hydrogen bond aggregation of the electrolyte, inhibit crystallization, and promote lithium salt dissociation. If EC is too low, the synergistic effect with the functional layer is insufficient, and the low-temperature modification effect is greatly weakened; if EC is too high, the electrolyte viscosity and crystallization tendency increase, offsetting the core regulatory effect of the functional layer.
[0057] For example, the mass percentage of ethylene carbonate (EC) in the above mixed solvent can be specifically selected as 20%, 30%, 40%, or any value between the two mentioned above.
[0058] The following detailed description of this application is based on specific embodiments, but the implementation and protection of this invention are not limited thereto. The following embodiments are only some embodiments of this application and are not intended to limit this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0059] Example 1 This embodiment provides a lithium-ion battery, which includes a housing and an electrode assembly and an electrolyte contained within the housing; the electrode assembly includes a positive electrode, a negative electrode, and a separator; the separator is disposed between the positive electrode and the negative electrode. The positive electrode uses lithium iron phosphate (LFP) positive electrode, and the specific material ratio (mass ratio) is: lithium iron phosphate (active material): acetylene black (conductive agent): polyvinylidene fluoride (PVDF, binder) = 95:3:2.
[0060] The negative electrode uses artificial graphite, and the specific material ratio (mass ratio) is: artificial graphite (active material): conductive carbon black (conductive agent): sodium carboxymethyl cellulose (CMC, dispersant): styrene-butadiene rubber (SBR, binder) = 96:1:1.5:1.5.
[0061] Both the positive and negative electrode sheets were prepared using conventional coating processes, with coating thicknesses of 120 μm (positive electrode) and 100 μm (negative electrode), respectively. The compacted densities after rolling were 2.2 g / cm³. 3 (Positive electrode), 1.6 g / cm 3 (negative electrode).
[0062] The electrolyte solute is LiPF6, and the solvent is a mixture of ethylene carbonate (EC, 30wt%), dimethyl carbonate (DMC, 40wt%), and ethyl methyl carbonate (EMC, 30wt%).
[0063] The membrane comprises a PE base membrane with a porosity of 45% and a functional layer disposed on at least one side of the PE base membrane along the thickness direction; the functional layer comprises polyethylene oxide with a number average molecular weight of 12,000, PEC with a number average molecular weight of 15,000, N-methyl-N'-hydroxyethyl urea, and glycidyl ether; and the mass ratio of polyethylene oxide to PEC is 1:5; glycidyl ether accounts for 2% of the total mass of PEO and PEC, and N-methyl-N'-hydroxyethyl urea accounts for 7% of the total mass of PEO and PEC.
[0064] The manufacturing process of the aforementioned lithium-ion battery is as follows: PEO and PEC were simultaneously added to DMF solvent, heated to 40°C, and stirred at 400 rpm for 3.5 h. At the same time, the mixture was ultrasonically dispersed at 400 W for 1.2 h to promote the uniform interpenetration and compatibility of PEO and PEC molecular chains, forming a continuous amorphous blend system, thus obtaining the PEO-PEC blend mother liquor.
[0065] The PEO-PEC blend mother liquor was kept at 40℃, and 2% glycidyl ether was added according to the total mass of PEO and PEC. Then, N-methyl-N'-hydroxyethyl urea was added according to the total mass of PEO and PEC. The mixture was kept at 40℃ and stirred for 2.5 h, while simultaneously being ultrasonically dispersed at 400 W and 40 kHz for 30 min to promote ring-opening of epoxy groups and covalent bond formation, forming a PEO-PEC-crosslinker-hydroxyethyl urea covalent network. After the reaction was completed, the temperature was lowered to 25℃ and stirred for 30 min to stabilize the system. The viscosity of the solution was measured to be 2000 mPa·s, yielding a hydroxyethyl urea-modified PEO-PEC mother liquor that can be directly used for coating.
[0066] The PE base film was heat-treated at 70℃ and 0.012MPa for 90 minutes to remove surface adsorbed moisture and then set aside for use. The modified mother liquor was coated onto both sides of the separator using a microgravure coating method, controlling the dry film thickness to 5μm. After coating, it was heat-treated at 70℃ and 0.012MPa for 90 minutes for drying. After drying, the separator was placed in a dry environment to cool to room temperature, obtaining the separator with the functional layer. The relative crystallinity of the functional coating at -40℃ was 6%, and the air permeability was 350s / 100mL.
[0067] The above-mentioned separator is assembled with the positive electrode and negative electrode to form a cell, electrolyte is injected, and after encapsulation, the target battery is obtained. The viscosity of the electrolyte at -40℃ to -20℃ is 50~100mPa·s.
[0068] Example 2 This embodiment is basically the same as Example 1, except that the amorphous polymer PEC is replaced with PTMC (number average molecular weight 15000). The other raw material specifications, preparation steps and parameters are the same as in Example 1, and the coated separator and the corresponding battery are prepared.
[0069] Example 3 This embodiment is basically the same as Example 1, except that the mass ratio of PEO to PEC is adjusted to 1:4, and the specifications of other raw materials, preparation steps and parameters are the same as in Example 1, so as to prepare the coated separator and the corresponding battery.
[0070] Example 4 This embodiment is basically the same as Example 1, except that the mass ratio of PEO to PEC is adjusted to 1:6, and the specifications of other raw materials, preparation steps and parameters are the same as in Example 1, so as to prepare the coated separator and the corresponding battery.
[0071] Example 5 This embodiment is basically the same as Example 1, except that the modifier N-methyl-N'-hydroxyethyl urea is replaced with N,N'-di(2-hydroxyethyl)-urea, and the amount used is still 7% of the total mass of PEO and PEC. The specifications of other raw materials, preparation steps and parameters are the same as in Example 1, and the coated separator and the corresponding battery are prepared.
[0072] Example 6 This embodiment is basically the same as Example 1, except that the crosslinking agent glycidyl ether is replaced with 1,4-butanediol diglycidyl ether (BDDGE), and the amount used is still 2% of the total mass of PEO and PEC. The specifications of other raw materials, preparation steps and parameters are the same as in Example 1, and the coated separator and the corresponding battery are prepared.
[0073] Example 7 This embodiment is basically the same as Example 1, except that: no hydroxyethyl urea (modifier) and glycidyl ether (crosslinking agent) are added during the preparation process. Only the PEO-PEC uncrosslinked blend system is prepared and coated on the surface of the separator. The specifications of other raw materials, preparation steps and parameters are the same as in Example 1. The coated separator and the corresponding battery are obtained.
[0074] Example 8 This embodiment is basically the same as Embodiment 1, except that the thickness of the functional layer dry film is controlled to be 2μm during coating. The other raw material specifications, preparation steps and parameters are the same as in Embodiment 1, and the coated separator and the corresponding battery are prepared.
[0075] Example 9 This embodiment is basically the same as Embodiment 1, except that the thickness of the functional layer dry film is controlled to be 10 μm during coating. The other raw material specifications, preparation steps and parameters are the same as in Embodiment 1, and the coated separator and the corresponding battery are prepared.
[0076] Comparative Example 1 This comparative example does not have any functional layer. It directly uses the same PE base film (porosity 45%) as the separator as in Example 1. The other raw materials (positive electrode, negative electrode, electrolyte) and battery assembly steps are the same as in Example 1, and a conventional battery is prepared.
[0077] Comparative Example 2 This comparative example is basically the same as Example 1, except that: the functional layer only uses PEO (number average molecular weight 12000) and no amorphous polymer (PEC) is added. The specifications of other raw materials, preparation steps and parameters are the same as those in Example 1, and the coated separator and the corresponding battery are prepared.
[0078] Comparative Example 3 This comparative example is basically the same as Example 1, except that the prepared hydroxyethyl urea modified PEO-PEC mother liquor is coated on the surface of the positive electrode and negative electrode, rather than the surface of the separator. The specifications of other raw materials, preparation steps and parameters are the same as in Example 1, and the corresponding battery is prepared.
[0079] Comparative Example 4 This comparative example is basically the same as Example 1, except that PEO and PEC are mixed into the active material layers of the positive and negative electrodes at a mass ratio of 1:5, and no separate functional layer is set. The specifications of other raw materials, preparation steps and parameters are the same as in Example 1, and the corresponding battery is prepared.
[0080] Comparative Example 5 This comparative example is basically the same as Example 1, except that: the functional layer only contains PEO, PEC and glycidyl ether (without hydroxyethyl urea). Hydroxyethyl urea is not added to the functional layer, but is directly added to the electrolyte at a ratio of 0.5 wt%. The specifications of the other raw materials, preparation steps and parameters are the same as those in Example 1, and the corresponding battery is prepared.
[0081] Comparative Example 6 This comparative example is basically the same as Example 1, except that the modifier hydroxyethyl urea is replaced with urea (a commonly used hydrogen bond donor), and the amount used is still 7% of the total mass of PEO and PEC. The specifications of other raw materials, preparation steps and parameters are the same as in Example 1, and the corresponding battery is prepared.
[0082] Comparative Example 7 This comparative example is basically the same as Example 1, except that the modifier hydroxyethyl urea is replaced with 1,6-hexanediol (containing only hydroxyl groups and no urea groups), and the amount used is still 7% of the total mass of PEO and PEC. The specifications of other raw materials, preparation steps and parameters are the same as in Example 1, and the corresponding battery is prepared.
[0083] Comparative Example 8 This comparative example is basically the same as Example 1, except that the modifier hydroxyethyl urea is replaced with tetramethyl urea (containing only urea groups and no hydroxyl groups), and the amount used is still 7% of the total mass of PEO and PEC. The specifications of other raw materials, preparation steps and parameters are the same as in Example 1, and the corresponding battery is prepared.
[0084] The performance of the functional coatings, separators, and lithium-ion batteries of Examples 1 to 9, and Comparative Examples 1 to 8 were tested. The test indicators and procedures are as follows: Test method for relative crystallinity of functional coatings at -40℃: The relative crystallinity of the functional coating at -40℃ is determined by differential scanning calorimetry (DSC), which can accurately quantify the low-temperature crystallization inhibition effect of PEO. It is compatible with the PEO-PEC / PTMC / PPC three-system. Amorphous polymers have no crystallization melting peaks and do not interfere with the test results.
[0085] The sample was first dried under vacuum at 70℃ and 0.012MPa for 11 hours to completely remove moisture and residual solvent. The entire process was carried out in an argon glove box with a water and oxygen content of ≤1ppm. Using a pure functional coating film consistent with the patented process, 8mg of sample was cut and sealed in an aluminum crucible.
[0086] The entire test was conducted under nitrogen protection at a rate of 50 mL / min. The temperature was first increased to 100 °C at a rate of 10 °C / min and held for 5 min to eliminate thermal history. Then, the temperature was decreased to -40 °C at a rate of 10 °C / min and held for 30 min to ensure that the sample reached a low-temperature thermodynamic steady state. Finally, the temperature was increased to 100 °C at a rate of 10 °C / min, and the heat flow curve was collected to obtain the characteristic melting enthalpy of PEO.
[0087] The relative crystallinity is calculated using the following formula: Xc(%) = ΔHm / (196.4 × w) PEO )×100%, where 196.4 J / g is the standard enthalpy of fusion of 100% PEO crystallization, w PEO ΔHm: Mass fraction of PEO in the coating; ΔHm: Enthalpy of PEO melting in the coating obtained by DSC test, J / g; Xc: Relative crystallinity of the functional coating, %.
[0088] Test principle: Using the theoretical enthalpy of complete crystallization of PEO in the coating as the denominator and the measured enthalpy of melting as the numerator, the actual crystallization ratio of PEO in the coating is calculated, that is, the relative crystallinity of the functional coating at -40℃.
[0089] Test method for capacity retention of lithium-ion batteries at -40℃: (1) Before the test, the battery was left to stand at 25°C for 2 hours, charged to the rated voltage at 0.3C constant current and constant voltage, left to stand for 1 hour, discharged to the cut-off voltage, and the discharge capacity at room temperature (reference capacity) was recorded.
[0090] (2) Place the battery in a low temperature test chamber, set the temperature to -40℃, and keep it at a constant temperature for 4 hours to ensure that the battery temperature is consistent with the test chamber temperature.
[0091] (3) Maintain a constant temperature of -40℃ and discharge at a constant current of 0.33C until the battery cutoff voltage, and record the low-temperature discharge capacity.
[0092] (4) Calculate the discharge capacity retention rate: Retention rate (%) = (-40℃ discharge capacity / room temperature reference capacity) × 100%.
[0093] Each test group should include at least 3 batteries, and the average value should be taken as the final result. During the test, the temperature fluctuation of the test chamber should be controlled to be ≤±2℃.
[0094] Diaphragm air permeability test method: The air permeability of the diaphragm was tested using the Göller method (according to GB / T21650.1-2022), which can accurately characterize the pore connectivity and coating blockage of the diaphragm. Before testing, the diaphragm was pretreated for 24 hours in an environment of 23℃ and 50% relative humidity to eliminate internal stress and surface moisture. During testing, a flat, wrinkle-free, and undamaged diaphragm sample was fixed on the sample holder of the air permeability tester, ensuring that the test area was sealed and leak-proof. The effective test area was a circular region with a diameter of 30 mm. Under a constant pressure difference of 1.23 kPa, the time required for 100 mL of dry air to pass through the diaphragm at a uniform rate was measured, with the unit being s / 100 mL. Five test points were randomly selected for each sample group, and the average value after removing the maximum and minimum values was taken as the air permeability of the diaphragm.
[0095] The test results are shown in Table 1.
[0096] Table 1 The above data shows that the various embodiments of the present invention exhibit significant performance differences compared to the comparative examples, clearly demonstrating the decisive role of the component design, structural parameters, and placement of the functional layer on the separator surface in the low-temperature performance of the battery. Example 1, as the optimal embodiment, has a separator permeability of 350 s / 100 mL after coating, falling within the preferred range of 200~500 s / 100 mL. This avoids excessive ion transport resistance due to pore blockage caused by the coating, while also ensuring the continuous uniformity of the functional layer. The relative crystallinity of the functional coating at -40℃ is only 6%, falling within the optimal range of 3%~13%, effectively suppressing low-temperature crystallization of PEO and preserving a continuous and stable ion transport channel. The corresponding discharge capacity retention rate at -40℃ reaches 65.3%, the highest among all groups. Example 2 replaces the amorphous polymer PEC... The coating of PTMC resulted in an air permeability of 360 s / 100 mL, a relative crystallinity of 8.1%, and a discharge capacity retention rate of 58.7%. Although slightly lower than Example 1, these were still far superior to the comparative examples, verifying the feasibility of PTMC as a candidate amorphous polymer. Examples 3 and 4 adjusted the PEO to PEC mass ratio to 1:4 and 1:6, respectively. After coating, the air permeability was 370 s / 100 mL and 340 s / 100 mL, the relative crystallinity was 8.9% and 4.3%, and the discharge capacity retention rates were 55.2% and 62.1%, respectively, all within the preferred parameter range, demonstrating that... A mass ratio of 4:1:6 can effectively balance the coordination sites of PEO and the anti-crystallization effect of amorphous polymers. Examples 5 and 6, by replacing the modifier and crosslinking agent respectively, showed air permeability of 355s / 100mL and 358s / 100mL after coating, with relative crystallinity of 7% and 7.2%, and discharge capacity retention of 63.5% and 62.8%, respectively, similar to the performance of Example 1. This confirms that the alternative modifier and crosslinking agent can exert equivalent covalent crosslinking and electrolyte regulation effects. Example 7, without adding any modifier or crosslinking agent, showed an air permeability of 420s / 100mL after coating, with relative crystallinity of 7%. The degree of crystallinity increased significantly to 12.5%, close to the upper limit, while the discharge capacity retention rate was only 40.6%, significantly lower than other examples. This indicates that the covalent network synergistically constructed by the modifier and crosslinking agent is the key to improving low-temperature performance. In Examples 8 and 9, the functional layer thickness was set to 2 μm and 10 μm, respectively. After coating, the air permeability was 320 s / 100 mL and 480 s / 100 mL, the relative crystallinity was 8.3% and 7.5%, and the discharge capacity retention rate was 56.4% and 54.1%, respectively. This shows that too thin a coating will lead to discontinuity of the functional layer, while too thick a coating will increase the ion transport resistance, both of which will affect the low-temperature modification effect.Comparative Example 1 uses a conventional PE-based membrane without a functional layer, and has no relative crystallinity data. Its discharge capacity retention rate at -40℃ is only 20.5%, highlighting the core role of the functional layer in improving low-temperature performance. Comparative Example 2's functional layer contains only PEO, without amorphous polymers. After coating, its air permeability is 400s / 100mL, and its relative crystallinity is as high as 35.7%, far exceeding the optimal range. Its discharge capacity retention rate is only 25.3%, proving that PEO alone cannot inhibit low-temperature crystallization and is insufficient to improve low-temperature performance. Comparative Example 3 coats the functional layer onto the electrode surface, and Comparative Example 4 mixes the functional layer components into the electrode interior. Both have an air permeability of 300s / 100mL after coating, and relative crystallinities of 14.5% and 16.1% respectively, exceeding the optimal range of 3%~13%. Their discharge capacity retention rates are only 32.4% and 28.9%, respectively, clarifying that the functional layer can only achieve synergistic effects with the separator and electrolyte when placed on the membrane surface, thus exerting the optimal low-temperature modification effect. 5. Hydroxyethyl urea was directly added to the electrolyte instead of the functional layer. After coating, the air permeability was 365 s / 100 mL, the relative crystallinity was 15.2%, and the discharge capacity retention rate was 35.8%. This indicates that hydroxyethyl urea can only continuously and stably regulate electrolyte hydrogen bonding and inhibit low-temperature crystallization when it is fixed in the membrane functional layer through a covalent network. Comparative Examples 6, 7, and 8 used urea, 1,6-hexanediol, and tetramethylurea to replace hydroxyethyl urea, respectively. All three lacked the bifunctional groups of hydroxyl and urea groups. After coating, the air permeability was 372 s / 100 mL, 380 s / 100 mL, and 375 s / 100 mL, respectively, and the relative crystallinity was 18.6%, 20.3%, and 19.1%, respectively, all of which were far higher than the preferred range. The discharge capacity retention rates were only 30.2%, 28.5%, and 29.7%, respectively. This fully demonstrates that the synergistic effect of the bifunctional groups of hydroxyethyl urea (hydroxyl and urea groups) is the core element for improving the low-temperature discharge performance of the battery. A single functional group cannot achieve the same technical effect. Overall, all embodiments conforming to the design of components, proportions, structure, and position of the present invention have a relative crystallinity of -40℃ functional coating controlled at 3%~13%, a membrane permeability of 200~500s / 100mL, and a discharge capacity retention rate at -40℃ that is much higher than that of the comparative embodiments, fully verifying the necessity and superiority of the technical solution of the present invention in improving the low-temperature performance of lithium-ion batteries.
[0097] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0098] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.
[0099] In the foregoing description of this specification, references to terms such as "one embodiment," "another embodiment," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment is included in at least one embodiment of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples, without contradiction. Additionally, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium-ion battery, characterized in that, The lithium-ion battery includes a housing and an electrode assembly and an electrolyte housed within the housing; The electrode assembly includes a positive electrode, a negative electrode, and a separator, wherein the separator is disposed between the positive electrode and the negative electrode; The diaphragm includes a diaphragm substrate and a functional layer disposed on at least one surface of the diaphragm substrate along the thickness direction; The functional layer comprises polyethylene oxide and an amorphous polymer; the amorphous polymer has a Tg ≤ -17℃.
2. The lithium-ion battery according to claim 1, characterized in that, The amorphous polymer includes at least one of polyethylene carbonate and polytrimethylene carbonate.
3. The lithium-ion battery according to claim 1, characterized in that, The number average molecular weight of the polyethylene oxide is 8000~15000.
4. The lithium-ion battery according to claim 1, characterized in that, The number average molecular weight of the amorphous polymer is 10,000 to 20,000.
5. The lithium-ion battery according to claim 1, characterized in that, The mass ratio of the polyethylene oxide to the amorphous polymer is 1:(4~6).
6. The lithium-ion battery according to claim 1, characterized in that, The functional layer further includes a modifier; the modifier includes compounds containing both hydroxyl and urea groups; preferably, the compounds containing both hydroxyl and urea groups include at least one of N-methyl-N'-hydroxyethyl urea, N,N'-bis(2-hydroxyethyl)-urea, and 1,3-dihydroxymethyl urea.
7. The lithium-ion battery according to claim 1, characterized in that, The functional layer further includes a crosslinking agent; the crosslinking agent includes glycidyl ether; preferably, the glycidyl ether includes at least one of 1,4-butanediol diglycidyl ether, polypropylene glycol diglycidyl ether, and glyceryl triglycidyl ether.
8. The lithium-ion battery according to any one of claims 1 to 7, characterized in that, The relative crystallinity of the functional layer at -40℃ is 3%~13%; And / or, the single-layer coating thickness of the functional layer is 2μm~10μm.
9. The lithium-ion battery according to any one of claims 1 to 7, characterized in that, The air permeability of the diaphragm is 200s / 100mL to 500s / 100mL.
10. The lithium-ion battery according to claim 1, characterized in that, The electrolyte includes an electrolyte salt and a solvent; Preferably, the electrolyte salt includes at least one of LiPF6, LiBF4, LiFSI, and LiTFSI; And / or, the solvent includes at least one of ethylene carbonate, diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate.
